Thuricin17 Production and Proteome Differences in Bacillus thuringiensis NEB17 Cell-Free Supernatant Under NaCl Stress - Subramanian, Sowmyalakshmi; Souleimanov, Alfred; Smith, Donald L. (Frontiers in Sustainable Food Systems, 2021)
Bacillus thuringiensis strain NEB17, produces a bacteriocin, thuricin 17 (Th17) and is known to promote the growth more effectively under salt stress conditions. In this study, bacterial salt stress tolerance screening and the possible changes in its secretome under two levels of NaCl stress was evaluated. The salt tolerance screening suggested that the bacterium is able to grow and survive in up to 900 mM NaCl. Thuricin 17 production at salt levels from to 100-500 mM NaCl was quantified using HPLC. Salt stress adversely affected the production of Th17 at levels as low as 100 mM NaCl; and the production stopped at 500 mM NaCl, despite the bacterium thriving at these salt levels. Hence, a comparative proteomic study was conducted on the supernatant of the bacterium after 42 h of growth, when Th17 production peaked in the control culture, as determined by LC-MS/MS. Optimal (salt free) bacterial culture served as a control and 200 and 500 mM NaCl as stress conditions. As salt levels increased, the major enzyme classes, transferases, hydrolases, lyases and ligases showed increased abundance as compared to the control, mostly related to molecular function mechanisms. Some of the notable up-regulated proteins in 500 mM NaCl stress conditions included an S-layer protein, chitin binding domain 3 protein, enterotoxins, phosphopentomutase, glucose 6-phosphate isomerase and bacterial translation initiation factor; while notable down-regulated proteins included hemolytic enterotoxin, phospholipase, sphingomyelinase C, cold shock DNA binding protein family and alcohol dehydrogenase. These results indicate that, as the salt stress levels increase, the bacterium probably shuts down the production of Th17 and regulates its molecular functional mechanisms to overcome stress. This study indicates that end users have the option of using Th17 as a biostimulant or the live bacterial inoculum depending on the soil salt characteristics, for crop production. The mass spectrometry proteomics data have been deposited to Mass Spectrometry Interactive Virtual Environment (MassIVE) with the dataset identifier PXD024069, and doi:10.25345/C5RB8T.